2011
DOI: 10.1007/s12552-011-9046-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Savings for White and Black Young Adults: An Early Look at Racial Disparities in Savings and the Potential Role of Children’s Development Accounts (CDAs)

Abstract: This paper explores predictors of young adults' savings using propensity score analysis and logistic regression with separate, longitudinal samples of whites and blacks aged 17-23 from the Panel Study of Income Dynamics. We ask who saves among adolescents and young adults and whether the likelihood of having a savings account and the amount saved in young adulthood can be predicted by two factors: (1) having a savings account during adolescence and (2) having families who own assets. The majority of white (90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 67 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…The significance of gender in explaining savings in matched accounts has not been consistently supported by empirical evidence. While most studies point to the importance of gender in affecting savings performance (Mills et al 2008; Han et al 2009; Huang 2010; Friedline and Elliott 2011), research on savings performance among poor families in sub-Saharan Africa (Ssewamala, Ismayilova, et al 2010; Ssewamala, Karimli, et al 2010) has found no significant variation in savings by gender. It is important to note that all of these studies use administrative data on savings (available through financial institutions) as opposed to self-reported data on saving performance.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of gender in explaining savings in matched accounts has not been consistently supported by empirical evidence. While most studies point to the importance of gender in affecting savings performance (Mills et al 2008; Han et al 2009; Huang 2010; Friedline and Elliott 2011), research on savings performance among poor families in sub-Saharan Africa (Ssewamala, Ismayilova, et al 2010; Ssewamala, Karimli, et al 2010) has found no significant variation in savings by gender. It is important to note that all of these studies use administrative data on savings (available through financial institutions) as opposed to self-reported data on saving performance.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from PSID, researchers have compared 1950s‐ and 1960s‐born cohorts regarding work and income, and found significant changes among women (Corcoran and Matsudaira, ). Saving behaviours, an important factor for financial independence, were different between white and black young adults (Friedline and Elliott, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, gaps in savings are evident when data is disaggregated by demographic characteristics. Among those aged 12 to 17, 40% of black young people and 44% of young people from lower‐income households had savings accounts, compared to 77% and 85% respectively of their white and higher‐income counterparts (Elliott ; Friedline ; Friedline and Elliott ; Friedline, Elliott, and Chowa ). While all young people experienced increases in savings account ownership by the time they reached ages 17 to 25, gaps by race and income remained (Friedline and Elliott ).…”
Section: Review Of Research On Young People's Savingsmentioning
confidence: 99%
“…A second caveat was identified in another study that examined savings for separate samples of whites ( n = 534) and blacks ( n = 469). Friedline and Elliott () found that savings accounts at ages 12 to 17 were predictive of savings accounts at ages 17 to 23 for whites, but not blacks. Instead, black young people's employment and household's net worth were predictive of savings account ownership and accumulated savings.…”
Section: Review Of Research On Young People's Savingsmentioning
confidence: 99%